Development of Android-Based E-Comic as a Learning Media for Pancasila Education to Improve Learning Outcomes for Class V Elementary Schools - Elsa Nasywa Charisa; Moh Fathurrahman (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2025)
Abstract: Improving student learning outcomes through the use of learning media is the focus of research, which also highlights the importance of recent innovations in this field. This research uses the research and development (R&D) method with the ADDIE model, which includes: analysis, design, development, implementation, and evaluation. The subjects of this research were twenty-four fifth-grade students from Pati Regency. The results of observations, interviews, questionnaires, and documentation were used to collect data. Data analysis techniques include feasibility tests, product validity tests, data normality tests, and paired sample t-tests. Media and material validation resulted in an average score of 94.37%, placing it in the "very appropriate" category. The validation results obtained were 97.75% of teachers and students in the "very feasible" category in terms of product suitability. The research results show that the average score of class V students increase after the use of learning media. Thus, the results of research in the Pancasila Education subject, which carries the material "Getting to Know the History of the Unitary State of the Republic of Indonesia (NKRI)," can be improved through the use of e-comics based on Android devices. Abstrak: Meningkatkan hasil belajar siswa melalui penggunaan media pembelajaran merupakan fokus dari penelitian ini, yang juga menyoroti pentingnya inovasi terkini di bidang tersebut. Penelitian ini menggunakan metode penelitian dan pengembangan (R&D) dengan model ADDIE, yang mencakup: analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek penelitian ini adalah dua puluh empat siswa kelas V SD dari Kabupaten Pati. Data dikumpulkan melalui observasi, wawancara, angket, dan dokumentasi. Teknik analisis data meliputi uji kelayakan, uji validitas produk, uji normalitas data, dan uji t sampel berpasangan. Validasi media dan materi menghasilkan skor rata-rata sebesar 94,37% yang termasuk dalam kategori "sangat layak." Hasil validasi dari guru dan siswa menunjukkan persentase sebesar 97,75% dalam kategori "sangat layak" dari segi kesesuaian produk. Hasil penelitian menunjukkan bahwa rata-rata nilai siswa kelas V meningkat setelah menggunakan media pembelajaran. Dengan demikian, hasil penelitian pada mata pelajaran Pendidikan Pancasila yang mengusung materi “Mengenal Sejarah Negara Kesatuan Republik Indonesia (NKRI)” dapat ditingkatkan melalui penggunaan e-komik berbasis perangkat Android.